2016
DOI: 10.1093/cid/civ1182
|View full text |Cite
|
Sign up to set email alerts
|

Early Evidence of Impact of Monovalent Rotavirus Vaccine in Togo

Abstract: Togo introduced monovalent rotavirus vaccine starting 19 June 2014. We compared all-cause acute gastroenteritis (AGE) hospitalizations and rotavirus-associated hospitalizations during the prevaccine period (July 2008-June 2014) to 1 year after vaccine introduction (July 2014-June 2015). The proportion of children with AGE who tested positive for rotavirus declined from 53% (645/1223) in prevaccine years to 36% (68/187) in the postvaccine year (P< .01). The decline only occurred in children <1 year of age who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Among the early introducing African countries, declines in RVA-associated AGE hospitalizations have been shown to range between 24% and 49% following the nationwide vaccine use [17]. The decline only occurred in children <1 year of age who were eligible for vaccination and was greatest during the rotavirus season months, supporting that it was associated with vaccine implementation [18]. In Kenya, a study conducted in the Western parts of the country revealed a 48% decline in the rotavirus related hospitalizations among children aged <5 years in the post-vaccine period [10].…”
Section: Discussionmentioning
confidence: 99%
“…Among the early introducing African countries, declines in RVA-associated AGE hospitalizations have been shown to range between 24% and 49% following the nationwide vaccine use [17]. The decline only occurred in children <1 year of age who were eligible for vaccination and was greatest during the rotavirus season months, supporting that it was associated with vaccine implementation [18]. In Kenya, a study conducted in the Western parts of the country revealed a 48% decline in the rotavirus related hospitalizations among children aged <5 years in the post-vaccine period [10].…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine is derived from a genotype G1P[8] strain but induces immunity against both homotypic and heterotypic rotavirus strains [ 22 ]. We therefore are expecting a drop in the number of gastroenteritis cases due to rotavirus infection after the introduction of the Rotarix vaccine [ 23 ]. Continued rotavirus surveillance is necessary to monitor the impact of the vaccine on the overall number of hospitalizations for severe gastroenteritis and for the emergence of new genotypes against which the available rotavirus vaccines may be less effective [ 24 ].…”
Section: Main Textmentioning
confidence: 99%
“…Similarly, there is early evidence to suggest that these vaccines will have a significant impact in preventing and reducing the health burden of severe AGE in developing countries in Africa, despite their lower efficacy in clinical trials in these settings. Post‐vaccine introduction studies in these African countries have reported reductions in all‐cause gastroenteritis ranging between 18% and 65% . Proportions in rotavirus‐associated hospitalisations have been shown to decline at rates ranging from 24% to 56%, with most reductions being pronounced in children aged <1 year .…”
Section: Introductionmentioning
confidence: 99%
“…Post-vaccine introduction studies in these African countries have reported reductions in all-cause gastroenteritis ranging between 18% and 65% [13][14][15][16][17][18][19][20]. Proportions in rotavirus-associated hospitalisations have been shown to decline at rates ranging from 24% to 56%, with most reductions being pronounced in children aged <1 year [17][18][19][21][22][23][24]. It is noteworthy that data from Botswana and Zambia have indicated a decline of 27-48% in in-hospital mortality from gastroenteritis at various sentinel hospitals [14,18].…”
Section: Introductionmentioning
confidence: 99%